Analysis of the Risk of Kidney Dysfunction due to Heparin vs Clopidogrel Therapy in Vascular Thrombosis Patients: A Retrospective Study - Maulana Kamri, Andi; Sukmawati, Sukmawati; Avifa, Serly (Jurnal KESANS : Kesehatan dan Sains, 2025)
Introduction: The repeated use of anticoagulants like heparin and antiplatelets such as clopidogrel in individuals with vascular thrombosis necessitates an evaluation of the nephrotoxicity risk. Objective: This study seeks to assess the impacts of heparin and clopidogrel on renal function. Method: This cohort retrospective design examined data from 120 individuals with vascular thrombosis who were administered heparin (n=60) or clopidogrel (n=60). Renal parameters (serum creatinine, eGFR) were evaluated prior to and following therapy. The statistical analysis employed a paired t-test and multivariate logistic regression, utilising a 95% confidence interval. Results and Discussion: The heparin cohort had a notable elevation in serum creatinine (1.8±0.4 vs 1.2±0.3 mg/dL; p=0.02) and a reduction in eGFR (45±12 vs 68±15 mL/min/1.73m²; p=0.01) in comparison to the clopidogrel group. Therapy exceeding 7 days elevated the incidence of renal impairment by 2.3-fold (OR: 2.3; 95% CI: 1.4-3.8) in the heparin cohort. The nephrotoxic impact of heparin is much greater in patients with cardiovascular comorbidities (p=0.04). Conclusion: Heparin presents a greater risk of inducing renal dysfunction than clopidogrel, particularly with prolonged usage and in individuals with concomitant conditions. Rigorous oversight of renal function and evaluation of alternate treatments are advised.